(untitled) (Journal of Science and Technology, 2016)
The study examined the relationship between market orientation and performance in the pharmaceutical industry in Ghana. The study employed both quantitative and qualitative research techniques. A semi-structured questionnaire was designed and distributed to firms in the pharmaceutical sector notably, manufacturers, wholesalers, prescription-only-medicine firms (POM) and over-the-counter shops (OTC). It was established that whereas an earlier study in 2001, found market orientation in the pharmaceutical industry in Ghana to be low (35%), the current study found that due to improved microeconomic indicators, market orientation in the industry has grown significantly to over 50%. The findings of the study also indicate a significant relationship between market orientation and performance of firms in the pharmaceutical industry, and further indicate that, the practice of market orientation in the various categories of the sector differs with an increase in size and organizational commitments of the firms involved. This study extends understanding of market orientation into a pharmaceutical setting and is one of the few studies on market orientation in the pharmaceutical sector emanating from a developing economy context and in a multi-strata approach.